Effects of age at first separation from parents on suicidal ideation, suicide planning and suicide attempts among left-behind children: the causal mediating effect of traumatic events - Mei Yang; Yuanyuan Wu; Jing Zeng; Yangxi Huang; Xinyan Xie; Miao Zhou; Bing Xiang; Xian Wu; Xiaobing Zhai; Jiangxue Wang; Yudu Liu (Family Medicine and Community Health)
Background To investigate the relationship of age at first separation from parents (AFSP) with suicidal ideation (SI), suicide planning (SP) and suicide attempts (SA) among left-behind children (LBC) in China and the mediating effect of traumatic events (TEs).Methods This cross-sectional study employed a multistage sampling method to conduct questionnaire surveys in six high-concentrated LBC provinces. Logistic regression and restricted cubic splines were performed to investigate the association of AFSP with SI, SP and SA, and meta-analysis (I2) was used to assess the heterogeneity. Causal mediation analysis (structural equation modelling) was used to evaluate the mediating effect of TEs, and bootstrap resampling was employed to assess the robustness of the causal mediation analysis.Results A total of 12 162 (6269 LBC) participants were included in this study; the prevalence rates of SI, SP and SA among LBC were 30.7%, 18.6% and 11.9%; and LBC had a higher risk of SI (OR: 1.32), SP (OR: 1.40) and SA (OR: 1.25) than non-LBC, all p<0.001. AFSP was negatively associated with SI, SP and SA, particularly peaking before 2 years old. LBC with AFSP <2 years old had a higher risk of SI (OR 2.65; 95% CI 2.17 to 3.24; p<0.001), SP (OR 2.63; 95% CI 3.36 to 4.29; p<0.001) and SA (OR 2.04; 95% CI 2.73 to 3.63; p<0.001). TEs mediated the increased risk of SI (average causal mediation effect (ACME) 0.03–0.07; proportion (Prop) 40–54%; all p<0.001), SP (ACME 0.03–0.06; Prop 39–61%; all p<0.001) and SA (ACME 0.02–0.04; Prop 53–80%; all p<0.01).Conclusions We found that AFSP was associated with SI, SP and SA, mediated by TEs. Our findings supported the necessity of reducing SI, SP and SA risks among LBC and highlighted the need to consider AFSPs and TEs in intervention strategies.